Literature as an Ethos with Reference To Select Kashmiri Romantic Literature - Khan , Mohd. Shams Uddoha (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Literature is a word used by most of us as a part of general convention, unaware of its actual as well as allegorical aspect. We, the humans, sometimes, are unable to grasp the true essence of literature. It is true that humans evolve literature and literature evolves human culture, history, behavior and sensibility. Both rely on each other and develop a symbiotic relationship. The treasure of literature has a vast record of human experiences, feelings and expressions. The paper aims to study literature through Kashmiri Romantic perspective. It aims to acknowledge the Romantic phase of literature in the valley, arraying and appreciating the humanistic values present in it.